Meat intake and risk of gastric cancer in the Stomach cancer Pooling (StoP) project. Issue 1 (22nd November 2019) - Ferro, Ana; Rosato, Valentina; Rota, Matteo; Costa, Ana Rute; Morais, Samantha; Pelucchi, Claudio; Johnson, Kenneth C.; Hu, Jinfu; Palli, Domenico; Ferraroni, Monica; Zhang, Zuo‐Feng; Bonzi, Rossella; et al.
Abstract : The consumption of processed meat has been associated with noncardia gastric cancer, but evidence regarding a possible role of red meat is more limited. Our study aims to quantify the association between meat consumption, namely white, red and processed meat, and the risk of gastric cancer, through individual participant data meta‐analysis of studies participating in the "Stomach cancer Pooling (StoP) Project". Data from 22 studies, including 11, 443 cases and 28, 029 controls, were used. Study‐specific odds ratios (ORs) were pooled through a two‐stage approach based on random‐effects models. An exposure‐response relationship was modeled, using one and two‐order fractional polynomials, to evaluate the possible nonlinear association between meat intake and gastric cancer. An increased risk of gastric cancer was observed for the consumption of all types of meat (highest vs . lowest tertile), which was statistically significant for red (OR: 1.24; 95% CI: 1.00–1.53), processed (OR: 1.23; 95% CI: 1.06–1.43) and total meat (OR: 1.30; 95% CI: 1.09–1.55). Exposure‐response analyses showed an increasing risk of gastric cancer with increasing consumption of both processed and red meat, with the highest OR being observed for an intake of 150 g/day of red meat (OR: 1.85; 95% CI: 1.56–2.20). This work provides robust evidence on the relation between the consumption of different types of meat and gastric cancer. Adherence to dietary recommendations to reduce meat consumption may contribute to a reduction in the burden of gastric cancer. Abstract : What's new? Consumption of processed meat has been associated with non‐cardia gastric cancer, but evidence regarding a possible role of red meat is more limited. Here, the authors explore associations between white, red, and processed meat consumption and gastric cancer risk through an individual participant data meta‐analysis of case‐control studies within the Stomach cancer Pooling Project. An increased risk of gastric cancer was observed with high intakes of red and processed meat, with further confirmation through the computational and graphical depiction of the exposure‐response associations. Adherence to dietary recommendations to reduce meat consumption may contribute to reducing the burden of gastric cancer.